Synthesis of a charring agent containing triazine and benzene groups and its intumescent flame retardant performance for polypropylene. (October 2022) - Yang, Tonghui; Wu, Yanpeng; Cheng, Yongchang; Huang, Tao; Yu, Bin; Zhu, Meifang; Yu, Hao
Highlights: A liner charring agent (ETDPCs) containing benzene and triazene is synthesized. ETDPCs exhibited excellent thermostability and char-forming ability. LOI value of 30.4% for PP is reached with optimal ratio of FR and ETDPCs (3:1). Synergistic effect of FR and ETDPCs suppresses the heat transfer and smoke release. The continuous and dense graphitic char layer endows it with a high barrier effect. Abstract: A novel linear triazine-based charring agent, N-Ethanolamine Triazine-4, 4-diaminodiphenylsulfone-piperazine copolymer hybrids (ETDPCs), was successfully synthesized and was combined with fire-retardant (FR) (mass ratio 2:1 of ammonium polyphosphate (APP) and melamine pyrophosphate (MPP)) to fabricate intumescent flame-retard PP composites at a 20 wt% loading, which exhibited excellent char-forming capacity and thermostability. The value of the limiting oxygen index (LOI) reached 30.4% and the vertical burning test (UL-94) passed V-0 grade for the PP2 sample with a mass ratio of FR to ETDPCs being 3:1. The cone calorimeter test revealed that the total heat release (THR) and total smoke release (TSR) of PP2 were significantly decreased by 61.8% and 87.9% compared with that of pure PP. The flame retardancy index (FRI) of PP2 was 12.2, showing an "Excellent" grade of flame retardancy. The thermogravimetric results showed that ETDPCs presented good char formation ability, and it would greatly increase the charring yield of PP when combined with FR due to the synergistic effect. The investigation of the structures and properties of char residues indicated that the continuous and compact char layer with high mechanical stability and low thermal conductivity, containing benzene and triazine derivatives, was formed for PP2 during combustion, which acted as a good barrier against the transmission of heat and volatiles and movement of high-temperature melt. This work expanded the avenue in the synthesis of high-efficiency charring agents and improved the intumescent flame retardancy of PP.